Disentangling the direct and indirect effects of task, individual, and organizational factors on occupational citizenship behavior - Smith, Bradley (Criminal justice policy review, 2020)
Organizational citizenship behaviors (OCBs) have been the subject of considerable research attention within business organizations. Much less attention has been directed at OCBs within criminal justice agencies, and even less research has addressed OCBs within police organizations. The present study uses survey data collected from 829 police officers in India to assess the antecedents of several dimensions of OCBs. Unlike most prior research, we use a path model in an effort to disentangle the direct and indirect effects of organizational justice, job demands and job resources, organizational justice, stress, and work attitudes on OCBs while controlling for officer personal characteristics. Our findings indicate that job satisfaction and organizational commitment are strong predictors of OCBs and that they mediate the effects of job stress, which did not directly influence OCBs. In addition, organizational justice factors exerted inconsistent effects on OCBs. Strategies for increasing the likelihood that officers will engage in OCBs are discussed.